Computational study of silver-catalyzed stereoselective hydroalkylation of alkynes: Pauli repulsion controlled Z/E selectivity. Issue 52 (4th June 2021) - Hu, Lingfei; Gao, Han; Hu, Yanlei; Lv, Xiangying; Wu, Yan-Bo; Lu, Gang
Abstract : The σ)(π Pauli repulsion is revealed as the dominant factor affecting the stereoselectivity of 1, 2-alkyl migration of alkynyl boronate complexes. This is due to the cationic silver induced unequal redistribution of alkyne π electron density. Abstract : The mechanism and origin of stereoselectivity of silver-catalyzed hydroalkylation of alkynes were computationally investigated at the B3LYP-D3BJ/6-311+G(d, p)-SDD//B3LYP/6-31G(d)-LANL2DZ level. The complex of alkynyl trialkylboronate with cationic silver is a key intermediate, which triggers the rate- and stereoselectivity-determining 1, 2-migration step. Energy decomposition analysis indicates that the difference of Pauli repulsion dominates the stereoselectivity.